GAGASAN MODERASI BERAGAMA DALAM BUDAYA MANGGARAI - Silvester Manca (Jurnal Alternatif Wacana Ilmiah Interkultural, 2022)
This study aims to describe and analyze the idea of religious moderation in the cultural perspective of Manggarai, Flores, East Nusa Tenggara. Using qualitative methods and with data collection techniques through in-depth interviews, the author found that the idea of religious moderation was not something entirely new in Manggarai culture. It was found that the Manggarai people have cultural wisdom which contains the idea of moderation that can be applied in the context of religious life. The idea of such moderation is contained in two things, namely in various expressions and in practice. The various expressions found clearly indicate that the Manggarai people have a clear concept of moderation, including religious moderation. That means that the religious moderation echoed by the government has a clear cultural basis in the context of Manggarai culture.